UMOD as a susceptibility gene for end-stage renal disease - Reznichenko Anna; Böger Carsten A; Snieder Harold; van den Born Jacob; de Borst Martin H; Damman Jeffrey; van Dijk Marcory CRF; van Goor Harry; Hepkema Bouke G; Hillebrands Jan-Luuk; Leuvenink Henri GD; Niesing Jan; et al. (BMC, 2012)
Abstract Background In recent genetic association studies, common variants including rs12917707 in the UMOD locus have shown strong evidence of association with eGFR, prevalent and incident chronic kidney disease and uromodulin urinary concentration in general population cohorts. The association of rs12917707 with end-stage renal disease (ESRD) in a recent case-control study was only nominally significant. Methods To investigate whether rs12917707 associates with ESRD, graft failure (GF) and urinary uromodulin levels in an independent cohort, we genotyped 1142 ESRD patients receiving a renal transplantation and 1184 kidney donors as controls. After transplantation, 1066 renal transplant recipients were followed up for GF. Urinary uromodulin concentration was measured at median [IQR] 4.2 [2.2-6.1] yrs after kidney transplantation. Results The rs12917707 minor allele showed association with lower risk of ESRD (OR 0.89 [0.76-1.03], p = 0.04) consistent in effect size and direction with the previous report (Böger et al, PLoS Genet 2011). Meta-analysis of these findings showed significant association of rs12917707 with ESRD (OR 0.91 [0.85-98], p = 0.008). In contrast, rs12917707 was not associated with incidence of GF. Urinary uromodulin concentration was lower in recipients-carriers of the donor rs12917707 minor allele as compared to non-carriers, again consistent with previous observations in general population cohorts. Conclusions Our study thus corroborates earlier evidence and independently confirms the association between UMOD and ESRD.